2012
DOI: 10.2466/01.07.21.pr0.110.2.677-693
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of Organizational Justice in a Call Center Context

Abstract: Summary.-Employees in three call centers were surveyed about their perceptions of organizational justice. Four factors were measured: distributive justice, procedural justice, interpersonal justice, and informational justice. Structural equation modeling was employed to test whether a two-, three-, or four-factor model best fit the call center data. A three-factor model of distributive, procedural, and informational justice provided the best fit to these data. The three-factor model that showed the best fit do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Since the dimensionality of Colquitt's Organizational Justice Scale has been tested in several studies with somewhat diverging results ( Judge and Colquitt, 2004;Blakely et al, 2005;Maharee-Lawler et al, 2010;Flint et al, 2012), the data were subjected to confirmatory factor analysis to examine its dimensionality in the context of the public health sector (for details see Enoksen, 2015). The analysis showed that the data of this study had a good fit with Colquitt's four-dimensional scale (RMSEA ¼ 0.06, x² ¼ 302, df ¼ 163, NFI ¼ 0.97, CFI ¼ 0.99).…”
Section: Perceived Discrimination Against Immigrantsmentioning
confidence: 99%
“…Since the dimensionality of Colquitt's Organizational Justice Scale has been tested in several studies with somewhat diverging results ( Judge and Colquitt, 2004;Blakely et al, 2005;Maharee-Lawler et al, 2010;Flint et al, 2012), the data were subjected to confirmatory factor analysis to examine its dimensionality in the context of the public health sector (for details see Enoksen, 2015). The analysis showed that the data of this study had a good fit with Colquitt's four-dimensional scale (RMSEA ¼ 0.06, x² ¼ 302, df ¼ 163, NFI ¼ 0.97, CFI ¼ 0.99).…”
Section: Perceived Discrimination Against Immigrantsmentioning
confidence: 99%
“…Colquitt (2001 ) aimed to address the problem of inconsistent and poor measurements by constructing a new four-dimensional Organizational Justice Scale based on seminal works in the organizational justice literature. The measure has been tested in several subsequent studies, but results regarding the dimensionality of the construct are diverging ( Judge & Colquitt, 2004 ;Blakely, Andrews, & Moorman, 2005 ;Maharee-Lawler, Rodwell, & Noblet, 2010 ;Flint, Haley, & McNally, 2012 ). Variation in research fi ndings may be due to context, as contextual diff erences may account for more vari-ation than individual diff erences across research sites ( Johns, 2006 ).…”
mentioning
confidence: 99%
“…Variation in research fi ndings may be due to context, as contextual diff erences may account for more vari-ation than individual diff erences across research sites ( Johns, 2006 ). Several researchers have argued the need for justice to be viewed contextually ( Hertel, Aarts, & Zeelenberg, 2002 ;Wang & Yao, 2011 ), and the dimensionality of organizational justice in particular may be more context-dependent than previously thought ( Flint, et al ., 2012 ). This study will test the dimensionality of Colquitt's Organizational Justice Scale in a public health sector context.…”
mentioning
confidence: 99%
“…Literature illustrated that interpersonal justice is related to aspects of human relationships such as; respect, politeness, caring and appreciating. Informational justice represents the explanations which are provided by managers to their employees about decisions and the availability of information within organizations (Flint, Haley and McNally, 2012).…”
Section: Organizational Justice Dimensionsmentioning
confidence: 99%